2020
DOI: 10.1002/psp4.12537
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of Systemic, Intracellular, and Lung Concentrations of Azithromycin With Different Dosing Regimens Used in COVID‐19 Clinical Trials

Abstract: Azithromycin (AZ), a broad-spectrum macrolide antibiotic, is being investigated in patients with coronavirus disease 2019 . A population pharmacokinetic model was implemented to predict lung, intracellular poly/mononuclear cell (peripheral blood monocyte (PBM)/polymorphonuclear leukocyte (PML)), and alveolar macrophage (AM) concentrations using published data and compared against preclinical effective concentration 90% (EC 90 ) for severe acute respiratory syndromecoronavirus 2 (SARS-CoV-2). The final model de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Specifically, a study showed AZM induced reduction in rhinovirus replication 7-fold in primary bronchial epithelial cells without inducing cell death ( Schögler et al, 2015 ). The in vitro EC50 for AZM against SARS‐CoV‐2 was 2.12µM (EC90: 8.65µM) following a 72‐hour incubation post-infection (MOI of 0.002) ( Hughes et al, 2020 ). The addition of AZM with HCQ was efficient in virus elimination in COVID-19 patients ( Gautret et al, 2020 ).…”
Section: Selected Antivirals Repurposing In Covid-19 Treatmentsmentioning
confidence: 99%
“…Specifically, a study showed AZM induced reduction in rhinovirus replication 7-fold in primary bronchial epithelial cells without inducing cell death ( Schögler et al, 2015 ). The in vitro EC50 for AZM against SARS‐CoV‐2 was 2.12µM (EC90: 8.65µM) following a 72‐hour incubation post-infection (MOI of 0.002) ( Hughes et al, 2020 ). The addition of AZM with HCQ was efficient in virus elimination in COVID-19 patients ( Gautret et al, 2020 ).…”
Section: Selected Antivirals Repurposing In Covid-19 Treatmentsmentioning
confidence: 99%
“…All of them received standard of care (SoC) as and when necessary, including anti-pyretic drugs for reducing fever, antihistamines for alleviating cough and Azithromycin (500 mg/day). Azithromycin was selected for its antiviral and anti-inflammatory properties and its wide use in COVID-19 patients with profound safety and moderate efficacy [11][12][13]. Further, patients of the "Hospitalized Group" received oxygen and management at the intensive care unit (ICU) as per the decision of the attending physicians.…”
Section: Methodsmentioning
confidence: 99%
“…Azithromycin (AZ)is a broad-spectrum antibiotic suggested recently to has a potential role in the management of COVID-19 with its antiinflammatory and antiviral activities. However, oral or parenteral use is associated with many adverse effects including cardiac toxicity [76][77][78].…”
Section: Inhaled Azithromycinmentioning
confidence: 99%